AB initio calculation of intermolecular potentials and prediction of second virial coefficients for dimmer H2-F2. - Tat, Phan Van (Vietnam Journal of Chemistry, 2012)
The results presented in this paper are the intermolecular potentials and the prediction of second virial coefficient, B2 (T) of the system H2-F2. The ab initio potentials were proposed from the quantum chemical calculations using at high level of theory CCSD(T) with basis sets of Dunning’s valence correlation-consistent aug-cc-pVmZ (m = 2, 3); the calculated ab initio energies were extrapolated to complete basis set limit aug-cc-pV23Z. The method MPn (n = 2, 3, 4) and other basis sets than 6-31G(d), Dunning’s basis sets cc-pVmZ (m = 2, 3) were also considered in the convergence of ab initio energies for the orientation T-shape, but the results presented inferior. The ab initio energies derived by the exponential extrapolation were used to construct the 5-site pair potential functions. The virial coefficients for this dimer were predicted from those with integration. The predicted virial coefficients were corrected to first-order quantum effects. The results turn out to be good agreement with experimental data and those from empirical correlation method. The quality of 5-site potentials proved the reliability for prediction of molecular thermodynamic properties.